ANALISIS STRATEGI PEMASARAN DALAM MENINGKATKAN KUNJUNGAN WISATAWAN DI WISATA GUNUNG PUNDUT (WGP) DINO PARK - Della Puspita Sari; Moh. Agung Surianto (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to analyze the marketing strategies implemented by Wisata Gunung Pundut (WGP) Dino Park in increasing tourist visits, with a focus on the 4P marketing mix (product, price, place, and promotion). The research applies a qualitative descriptive approach using interviews, observations, and documentation with management, social media administrators, and visitors (both new and repeat). The results show that although WGP Dino Park has implemented marketing strategies, there are several shortcomings. Facilities for accompanying adults are inadequate, ticket prices are affordable but lack repeat-visit promotions, road access is narrow, and promotional efforts have not reached wider audiences. These findings suggest the need for facility improvements, loyalty programs, and wider collaboration with schools and travel agents. The implication is that WGP Dino Park needs integrated marketing strategies to build sustainable visitor engagement and increase repeat visits.